Implementasi e-Kinerja dalam Peningkatan Kinerja Aparat Sipil Negara (ASN) di Kantor Camat Sinjai Selatan - Juz Ayini Asrianty; Syamsuddin Syamsuddin; Sumardi Sumardi (Varied Knowledge Journal, 2026)
The implementation of e-Kinerja as part of bureaucratic reform and the Electronic-Based Government System (SPBE) is expected to improve the performance of the Civil Service (ASN). However, studies on the implementation of e-Kinerja both as a policy implementation process and in terms of its contribution to improving ASN performance at the subdistrict level remain limited. This study aims to analyze the implementation of e-Kinerja at the South Sinjai Subdistrict Office and its contribution to improving ASN performance. The study employs a qualitative method using a case study approach. Data were collected through observation, in-depth interviews, and documentation from 12 informants selected via purposive sampling, and were subsequently analyzed using the Miles and Huberman interactive model. Policy implementation was analyzed using George C. Edward’s model, while performance improvement was analyzed through Armstrong’s perspective. The results indicate that the implementation of e-Kinerja has been effective, supported by good communication, an adaptive attitude among implementers, and a clear bureaucratic structure, although it still faces challenges such as limited supporting facilities, internet connectivity, and employees’ digital literacy. The implementation of e-Kinerja contributes to improving civil servant performance by strengthening performance planning, monitoring, reporting, and evaluation, which in turn leads to improved performance outcomes and employee discipline. However, the use of evaluation results for the coaching and competency development of civil servants still needs to be optimized to support continuous performance improvement.